Everything all at once - Leno, Katrina (HarperTeen, an imprint of HarperCollinsPublishers, 2017)
When her struggles with anxiety worsen in the aftermath of a family death, Lottie is bequeathed a series of letters from her late aunt, a best-selling author, who leaves instructions to help Lottie overcome her fears and explore her own literary voice